Oxidation of Polyunsaturated Fatty Acids as a Promising Area of Research in Infertility - Giulia Collodel; Elena Moretti; Daria Noto; Roberta Corsaro; Cinzia Signorini (MDPI AG, 2022)
In this review, the role of fatty acids (FA) in human pathological conditions, infertility in particular, was considered. FA and FA-derived metabolites modulate cell membrane composition, membrane lipid microdomains and cell signaling. Moreover, such molecules are involved in cell death, immunological responses and inflammatory processes. Human health and several pathological conditions are specifically associated with both dietary and cell membrane lipid profiles. The role of FA metabolism in human sperm and spermatogenesis has recently been investigated. Cumulative findings indicate F2 isoprostanes (oxygenated products from arachidonic acid metabolism) and resolvins (lipid mediators of resolution of inflammation) as promising biomarkers for the evaluation of semen and follicular fluid quality. Advanced knowledge in this field could lead to new scenarios in the treatment of infertility.